Microbial Synthesis of Silver Nanoparticles Using Alternaria alternata and Their Characterization - Sarafadeen O. Kareem; Oluwagbenga T. Familola; Adejare R. Oloyede; Enock O. Dare (Applied Environmental Research, 2019)
In this study, extracellular biosynthesis of silver nanoparticles (AgNPs) was carried out using Alternaria alternata. AgNPs were synthesized using vegetative and cell-free filtrate methods. Silver nitrate (AgNO3) solution was reduced with fungal mycelial mass and cellfree filtrate at a ratio of 1:4 (v/v). Further, the effects of biosynthesis parameters (reaction time, reaction temperature, light and dark incubation, and static and agitated conditions) were determined. The structural integrity of the synthesized AgNPs was investigated through UVvisible spectrophotometry, X-ray diffraction (XRD) analysis, and transmission electron microscopy (TEM). Parameter optimization revealed that cell-free filtrate AgNP synthesis at 40 °C with constant agitation and incubation in darkness for 120 h using 1 mM AgNO3 resulted in the highest absorbance value (at 400 nm). Further, TEM images showed that the synthesized AgNPs were spherical, homogeneous, and well dispersed while the XRD peaks confirmed the purity of the AgNPs obtained. The diameters of the AgNPs were found to range from 7.48 to 12.15 nm. This study identifies Alternaria alternata as a potential candidate for use in the industrial biosynthesis of AgNPs.